Pengaruh Pelatihan Terhadap Kinerja Karyawan Pada PT. Wangsa Jatra Lestari Sukoharjo - Anggi Septiana Sari; R. Taufiq Nur Mufityanto; Agus Suyatno (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
In the current era of globalization, an organization is dynamic in responding to change in order to survive and achieve organizational goals. There are internal and external factors that influence organizational change, so an organization must respond well and appropriately to every change that arises. This research uses quantitative methods. A population is a group of individuals with different characteristics that are of interest in a study. The population in this study was 194 people. A sample is a portion of the population taken through certain methods that also has certain characteristics. The Slovin formula was used to eliminate several percent of the population that had to be sampled so that 66 respondents were obtained. The results of the coefficient of determination test for the dependent variable can be influenced by variables of 0.663 or 66,3%, while the remaining 33,7% is influenced by other variables. In the F test, the Fcount score is 129,071 > 3.14 and the significant value is 0.000 < 0.05. So it can be explained that H0 is rejected and H1 is accepted, which means that training has a positive and significant effect on performance and the model is said to be feasible. The results of the t test show that training has a t-count value of 11,361 t table of 1.66980 and a significant value of 0.000 < 0.05, so it can be concluded that training has a significant influence on employee performance.